The complete mitochondrial genome of Sarcophaga caerulescens (Diptera: Sarcophagidae) - Shujuan Wang; Zhiyun Pi; Yanjie Shang; Xiangyan Zhang; Changquan Zhang; Yadong Guo; Jifeng Cai (Mitochondrial DNA. Part B. Resources, 2022)
Sarcophaga caerulescens (Zetterstedt 1838) (Diptera: Sarcophagidae) belongs to Sarcophagidae, which is closely associated with human life in ecological habits and has a clear environmental preference. Sarcophaga caerulescens can be better correlated with migration and postmortem interval (PMI) inference in forensic practice. In this study, we reported the complete mitochondrial genome (mitogenome) of S. caerulescens. The length of this mitogenome was 15,720 bp in total (GenBank accession No. MW551788), containing 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and a non-coding control region. Its nucleotide composition was A (39.7%), C (14.1%), G (9.4%), and T (36.9%). The phylogenetic relationships indicated that the species of S. caerulescens was closely related to S. similis. This study provides the mitochondrial data of S. caerulescens for further study of mitochondrial genome and enriches our understanding of the phylogenetic relationship of sarcophagid flies.